2016
DOI: 10.2147/ijn.s102844
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic intrafibrillar/extrafibrillar mineralization of collagen scaffolds based on a biomimetic strategy to promote the regeneration of bone defects

Abstract: The mineralization of collagen scaffolds can improve their mechanical properties and biocompatibility, thereby providing an appropriate microenvironment for bone regeneration. The primary purpose of the present study is to fabricate a synergistically intra- and extrafibrillar mineralized collagen scaffold, which has many advantages in terms of biocompatibility, biomechanical properties, and further osteogenic potential. In this study, mineralized collagen scaffolds were fabricated using a traditional mineraliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 62 publications
2
44
0
1
Order By: Relevance
“…The X-ray diffraction (XRD) peaks of collagen-coated GF confirmed that they existed in separate planes. In addition, they did not interact with each other which is supported by their distinct peak positions without any considerable change that is supported by the above references [ 33 , 35 , 36 ].…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…The X-ray diffraction (XRD) peaks of collagen-coated GF confirmed that they existed in separate planes. In addition, they did not interact with each other which is supported by their distinct peak positions without any considerable change that is supported by the above references [ 33 , 35 , 36 ].…”
Section: Resultssupporting
confidence: 52%
“…The two diffraction peaks at 2 θ = 26.5° and 2 θ = 55° correspond to the (002) and (004) planes of graphene, respectively, where the intensity of the peak at 2 θ = 26.5° got reduced for the collagen coating [ 33 , 35 ]. The diffraction peaks of collagen appeared to correspond to the crystallographic planes (211) and (222) at about 2 θ = 32° and 2 θ = 45.3° indicating a traditional mineralized collagen [ 36 ]. The X-ray diffraction (XRD) peaks of collagen-coated GF confirmed that they existed in separate planes.…”
Section: Resultsmentioning
confidence: 99%
“…Collagen has also been utilized in guided bone regeneration procedures due to their biodegradability, osteoconduction, and osteoinduction (Ferreira et al, 2012 ). Collagen scaffolds provide an ideal environment for bone formation (Wang et al, 2016 ). They also serve as the best carrier for targeted delivery of small molecules such as antagonists of miR-16, which increases the relative levels of Runx2 and osteocalcin, thereby promoting mineral calcium deposition (Mencía Castaño et al, 2019 ).…”
Section: Natural Polymers: Organic Biomaterials Extracted From Organismentioning
confidence: 99%
“…Among these, scaffolds play a crucial role in tissue engineering by mimicking the function of the extracellular matrix (ECM), and by offering a three-dimensional spaciotemporal microenvironment for cell attachment, migration, proliferation, differentiation, and metabolism1314 A suitable scaffold also has other characteristics including a highly porous interconnected network with proper surface properties, biocompatibility, and biodegradability harmonious with the rate of cell/tissue growth and maturation 1115. Collagen, a significant constituent of the natural ECM, has been regarded as the ideal material for soft tissue engineering constructs due to its excellent biocompatibility and biodegradability 161718. However, collagen-based scaffolds have a crucial limitation on the use of artificial substitutes because of its high degradation rate and poor mechanical properties 161718.…”
Section: Introductionmentioning
confidence: 99%
“…Collagen, a significant constituent of the natural ECM, has been regarded as the ideal material for soft tissue engineering constructs due to its excellent biocompatibility and biodegradability 161718. However, collagen-based scaffolds have a crucial limitation on the use of artificial substitutes because of its high degradation rate and poor mechanical properties 161718. Therefore, the crosslinking of collagen is an effective strategy to modify the drawbacks and provide strength, reinforcement, and stabilization to the fibrils enough to be used as biomaterials 1719.…”
Section: Introductionmentioning
confidence: 99%